British Society of Gastroenterology guidelines for oesophageal manometry and oesophageal reflux monitoring. Issue 10 (31st July 2019) - Trudgill, Nigel J; Sifrim, Daniel; Sweis, Rami; Fullard, Mark; Basu, Kumar; McCord, Mimi; Booth, Michael; Hayman, John; Boeckxstaens, Guy; Johnston, Brian T; Ager, Nicola; De Caestecker, John
Abstract : These guidelines on oesophageal manometry and gastro-oesophageal reflux monitoring supersede those produced in 2006. Since 2006 there have been significant technological advances, in particular, the development of high resolution manometry (HRM) and oesophageal impedance monitoring. The guidelines were developed by a guideline development group of patients and representatives of all the relevant professional groups using the Appraisal of Guidelines for Research and Evaluation (AGREE II) tool. A systematic literature search was performed and the GRADE (Grading of Recommendations Assessment, Development and Evaluation) tool was used to evaluate the quality of evidence and decide on the strength of the recommendations made. Key strong recommendations are made regarding the benefit of: (i) HRM over standard manometry in the investigation of dysphagia and, in particular, in characterising achalasia, (ii) adjunctive testing with larger volumes of water or solids during HRM, (iii) oesophageal manometry prior to antireflux surgery, (iv) pH/impedance monitoring in patients with reflux symptoms not responding to high dose proton pump inhibitors and (v) pH monitoring in all patients with reflux symptoms responsive to proton pump inhibitors in whom surgery is planned, but combined pH/impedance monitoring in those not responsive to proton pump inhibitors in whom surgery is planned. This work has been endorsed by the Clinical Services and Standards Committee of the British Society of Gastroenterology (BSG) under the auspices of the oesophageal section of the BSG.